Cloud-Based ERP System Backend Design, study case: PT Cranium Royal Aditama - Manoppo, Arnoldus Yitzhak Petra; Istiono, Wirawan (ULTIMATICS, 2023)
An ERP system is a comprehensive software solution that facilitates the integration of all resources inside a firm. PT Cranium Royal Aditama is a company specializing in the development of Enterprise Resource Planning (ERP) solutions for other businesses. The ERP system of Cranium was constructed on the .Net architecture. Nevertheless, the situation remains unchanged. The Net framework is constrained by its compatibility exclusively with the Windows operating system. Cranium developed a cloud-based ERP system using Java programming language to ensure flexibility and compatibility with all operating systems. The backend of the ERP system is constructed utilizing a monolithic modular architecture, employing Java Springboot as a framework and PostgreSQL as the database. The purchasing, inventory control, and production planning modules are responsible for the design and development process. The design and development of the ERP system backend is now underway, however it is still in the development stage and is currently confined to a basic CRUD technique